Physiological and transcriptomic analyses revealed gene networks involved in heightened resistance against tomato yellow leaf curl virus infection in salicylic acid and jasmonic acid treated tomato plants - Wang, Peng; Sun, Sheng; Liu, Kerang; Peng, Rong; Li, Na; Hu, Bo; Wang, Lumei; Wang, Hehe; Afzal, Ahmed Jawaad; Geng, Xueqing (Frontiers in Microbiology, 2022)
Tomato yellow leaf curl virus (TYLCV), a member of the genus Begomovirus of the Geminiviridae family, causes leaf curl disease of tomato that significantly affects tomato production worldwide. SA (salicylic acid), JA (jasmonate acid) or the JA mimetic, COR (coronatine) applied exogenously resulted in improved tomato resistance against TYLCV infection. When compared to mock treated tomato leaves, pretreatment with the three compounds followed by TYCLV stem infiltration also caused a greater accumulation of H2O2. We employed RNA-Seq to identify DEGs (differentially expressed genes) induced by SA, JA, COR pre-treatments after Agro-inoculation of TYLCV in tomato. To obtain functional information on these DEGs, we annotated genes using GO and KEGG databases. Based on our comparative analysis, differentially expressed genes related to cell wall metabolism, hormone signaling and secondary metabolism pathways were analyzed in compound treated samples. We also found that TYLCV levels were affected in SlNPR1 and SlCOI1 silenced plants. Interestingly, compared to the mock treated samples, SA signaling was hyper-activated in SlCOI1 silenced plants which resulted in a significant reduction in viral titer whereas in SINPR1 silencing tomato plants, there was a 19-fold increase in viral load. Our results indicated that SA, JA and COR had multiple impacts on defense modulation at the early stage of TYLCV infection. These results will help us better understand SA and JA induced defenses against viral invasion and provide a theoretical basis for breeding viral resistance into commercial tomato accessions.